Vertical distribution of volatile organic compounds within the lower troposphere in late spring of Shanghai. (August 2018) - Zhang, Kun; Xiu, Guangli; Zhou, Lei; Bian, Qinggen; Duan, Yusen; Fei, Dongnian; Wang, Dongfang; Fu, Qingyan
Abstract: Air pollution has become one of the most stubborn environmental problem in China, the traditional environmental monitoring mainly focus on the horizontal distribution of the pollutants, while it is still of great importance to have the knowledge of the vertical profiles of them. The present study, for the first time, attempted to acquire the vertical distributions of O3 and one of its precursors, volatile organic compounds (VOCs) within 1000 m of lower troposphere by using a tethered balloon in the suburban of Shanghai, a Chinese megacity. We analyze the concentration and the ozone formation potential (OFP) at three height level of 50–350, 350–700, and 700–1000 m. According to our measurement, the total concentration of VOC decreased with the altitude increasing. In addition, the dominant species of OFP was alkene, aromatics, and alkene at height level of 50–350, 350–700 and 700–1000 m, respectively. Our results suggest that, in the morning, the fresh emission contributed a lot to the high concentration of benzene and toluene near ground. Furthermore, the regression analyzes showed toluene decreased faster than benzene in the troposphere. The VOC concentration can be used as initial values for numerical simulations of chemical reaction in the lower troposphere. Graphical abstract: Image 1 Highlights: We used a tethered balloon for monitoring the vertical profiles of VOCs. The concentration and OFP of VOCs at different altitude was analyzed. Toluene decreased quicker than benzene in the troposphere.